Pengaruh Literasi Pajak dan Digitalisasi Pajak Terhadap Kepatuhan Calon Wajib Pajak - Anisa Nur Setyani; Osmad Muthaher (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
This study aims to analyze the influence of tax literacy and tax digitalization on the compliance of prospective taxpayers based on thel perceptions of students as prospective taxpayers in the future. This study uses a quantitative method, with active students of the Faculty of Economics UNISSULA as the research population. Sampling used the purposive sampling method and obtained 96 samples. Data collection was carried out by distributing questionnaires online using Google Forms. The analytical method used in this study is the multiple linear regression analysis method conducted using the IBM SPSS 26 application. Where the results of the study indicate that tax literacy has been proven to have a significant effect on the compliance of prospective taxpayers, as well as the variable of tax digitalization, which has also been shown to have a significant influence on the compliance of prospective taxpayers. Suggestions for further research are to involve respondents with more diverse characteristics and to add other variables believed to improve compliance of prospective taxpayers.